Mummies tell stories: CT investigation of eight members of the Kėdainiai elite (Grand Duchy of Lithuania, 17th-18th centuries AD) - Piombino-Mascali, Dario; Girčius, Rokas; Tamošiūnas, Algirdas; Jankauskas, Rimantas; Brindzaitė, Rūta; Kozakaitė, Justina (Frontiers in Medicine, 2025)
The objective of this study is to evaluate the mummified remains of eight high-ranking people buried in two crypts of the Evangelical Reformed Church at Kėdainiai, Lithuania. The evaluation criteria include biological or cultural indicators, the assessment of pathological conditions and their possible etiology, and the preservation status of these remains. The eight individuals were recovered during a project aimed at exploring the tombs of potential members of the Radziwiłł family, a powerful dynasty of the former Grand Duchy of Lithuania and the Crown of the Kingdom of Poland (1569–1795). However, the remains could also belong to other affluent citizens of Kėdainiai who were buried in the same church between the 17th and 18th centuries. The deceased were investigated using classical anthropological methods and computed tomography, which allowed for a more nuanced vision of both individual social status and bio-histories for this assemblage. The results identify one case of post-mortem manipulation, evidence of significant pathological changes, including degenerative joint disease, lung and arterial calcifications, and neoplasias that would not have been visible without a paleoradiological approach. The historical context, as well as comparative clinical cases, helped narrow down the diagnoses proposed for the lesions concerned, and will be crucial to address additional histological or biomolecular research, should this be carried out in the future. Additionally, the study highlights the need for regular monitoring of the remains, particularly given the evident decay observed over the past four decades. This adds to the body of research suggesting that the more frequent inspection of individuals in which socioeconomic status can be assumed through mortuary context is warranted. In sum, this investigation shows that paleopathology, coupled with paleoradiology, provides a more permanent data set that enhances the interpretation of pathological conditions in preserved bodies, especially when they are in physical danger due to environmental or political changes.